CRIANÇAS QUE NÃO APRENDEM NA ESCOLA: PROBLEMATIZANDO PROCESSOS DE MEDICALIZAÇÃO E PATOLOGIZAÇÃO DAS INFÂNCIAS - Duarte, Beatriz Pombo Spinasse (2020)
The present research problematizes how the processes of medicalization of education in the face of childhood pathologization and difference are experienced in the researched daily life. We mean by medicalization the artificial transformation of issues fro